RECRUITMENT OF INTERNATIONAL MEMBERS OF FACULTY - Vladimir D. Khizhnyak (Высшее образование в России, 2016)
The article discusses the key factors of successful recruitment of international members of Faculty and the main stages of the process of search and employment of international employees. The article is written on the basis of the analysis of experience of foreign and Russian universities successfully attracting foreign specialists for extending length of time.